2014
DOI: 10.7863/ultra.33.10.1851
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of the Accessory Head of the Biceps Brachii

Abstract: Anatomic variations in the anterior aspect of the shoulder, such as an accessory head of the biceps brachii muscle, are not uncommon. The magnetic resonance imaging and arthroscopic appearance of the accessory head of the biceps brachii has been recently described. This series demonstrates the sonographic appearance of the accessory head of the biceps brachii in the bicipital groove. It is an asymptomatic, flat, echogenic structure with average measurements of 7.7 × 1.2 mm in cross section. Knowledge of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…Despite its close relationship with the long head of the biceps in the bicipital groove, anatomic dissections including ours have demonstrated that this structure has no anatomic connection with the biceps muscle but rather with the supraspinatus tendon proximally 2 4 . The third head of the biceps mentioned in the “Discussion” section of this article 1 is a completely different structure, as illustrated in the Figure 10 of our article 2 . For these reasons, we suggest that the terminology of aponeurotic expansion of the supraspinatus tendon should be preferred over that of accessory head of the biceps tendon.…”
Section: To the Editormentioning
confidence: 68%
See 1 more Smart Citation
“…Despite its close relationship with the long head of the biceps in the bicipital groove, anatomic dissections including ours have demonstrated that this structure has no anatomic connection with the biceps muscle but rather with the supraspinatus tendon proximally 2 4 . The third head of the biceps mentioned in the “Discussion” section of this article 1 is a completely different structure, as illustrated in the Figure 10 of our article 2 . For these reasons, we suggest that the terminology of aponeurotic expansion of the supraspinatus tendon should be preferred over that of accessory head of the biceps tendon.…”
Section: To the Editormentioning
confidence: 68%
“…We read with great interest the article by Lutterbach‐Penna et al 1 and congratulate the authors on their work. Our article 2 describing the exact same structure under a different terminology was recently published, and we would like to make a few constructive comments:…”
Section: To the Editormentioning
confidence: 99%
“…Si bien el músculo bíceps braquial puede ser estudiado por imágenes, ya sea ecografía como tomografía computada y resonancia nuclear magnética, los variaciones relatadas son hechas a través de la disección cadavérica (Brasseur, 2012;Catli et al, 2012;Lutterbach-Penna et al, 2014).…”
Section: Resultados Y Discusiónunclassified
“…This structure is often missed or mistakenly referred to as a bifid tendon or split tear of the LHB in case reports, case series, and small retrospective studies. [ 3 4 5 6 7 8 ] However, recent literature considers we should prefer the terminology of aponeurotic expansion or slip of the supraspinatus tendon, as described for the first time by Brodie in 1890, because it is not connected to the LHB despite its anatomical proximity. [ 2 9 10 ] A retrospective study of 150 shoulder magnetic resonance imaging (MRI) performed for various reasons at one institution and 50 US on cadaveric shoulders revealed that aponeurotic expansion of the supraspinatus located anterior and lateral to the LHB in its groove can be identified in about half of the shoulders on MRI or US.…”
Section: Discussionmentioning
confidence: 99%